Cubic boron nitride sintered body and method for producing the same
By adopting cubic crystal boron nitride sintered body treated with specific composition and process, the problem of short tool life in high-strength cast iron material processing is solved, and the tool life is achieved is long, suitable for the high-performance and lightweight automotive industry.
Patent Information
- Application Number
- CN201980103060.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-12-27
AI Technical Summary
In the high-efficiency processing of high-strength cast iron materials, existing tools have short lifespans and are difficult to meet the needs of high-performance and lightweight automotive industry.
A cubic-crystal boron nitride sintered body having a cubic-crystal boron nitride particles of 40% or more and 96% or less and a combined phase of 4% or more and 60% or less is used, and a specific heating and pressurization step includes heating and pressurization in a stable region of wurtzite type boron nitride, and the burst temperature to the stable region is set to 600°C or more.
The tool life is achieved, and the tool life can be significantly extended even in the high-efficiency processing of high-strength cast iron materials.
Smart Images

Figure CN114845973B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a cubic boron nitride sintered body and a method for producing the same. Background Art
[0002] Cubic boron nitride (hereinafter also referred to as "cBN") has very high hardness and excellent thermal and chemical stability, and is therefore used for cutting tools and wear-resistant tools.
[0003] International Publication No. 2012 / 053375 (Patent Document 1) discloses a sintered body formed by sintering cubic boron nitride particles with a binder phase. In Patent Document 1, wear resistance and defect resistance were successfully improved by adjusting the composition of the binder phase.
[0004] In Japanese Patent Publication No. 2005-187260 (Patent Document 2) and International Publication No. 2005 / 066381 (Patent Document 3), in a cubic boron nitride sintered body (hereinafter also referred to as "cBN sintered body") formed by sintering cBN particles as a binding phase, the wear resistance and defect resistance were successfully improved by adjusting the amount of catalyst elements in the cBN particles.
[0005] Japanese Patent Application Publication No. 2015-202980 (Patent Document 4) and Japanese Patent Application Publication No. 2015-202981 (Patent Document 5) disclose a cBN sintered body obtained by mixing hexagonal boron nitride (hereinafter, also referred to as "hBN") powder and a binder powder and sintering the mixture under ultra-high temperature + ultra-high pressure conditions. The cBN sintered body contains a small amount of wurtzite boron nitride (hereinafter, referred to as "wBN") and high-strength cBN particles, thereby improving wear resistance and defect resistance.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2012 / 053375
[0009] Patent Document 2: Japanese Patent Application Publication No. 2005-187260
[0010] Patent Document 3: International Publication No. 2005 / 066381
[0011] Patent Document 4: Japanese Patent Application Publication No. 2015-202980
[0012] Patent Document 5: Japanese Patent Application Publication No. 2015-202981 Summary of the invention
[0013] The cubic boron nitride sintered body disclosed herein comprises 40% by volume or more and 96% by volume or less of cubic boron nitride particles and 4% by volume or more and 60% by volume or less of a binding phase, wherein:
[0014] The dislocation density of the cubic boron nitride particles is less than 1×10 15 / m 2 .
[0015] The method for producing a cubic boron nitride sintered body disclosed in the present invention is the method for producing a cubic boron nitride sintered body as described above, wherein:
[0016] The method for producing a cubic boron nitride sintered body comprises:
[0017] A process of preparing hexagonal boron nitride powder and bonding material powder; and
[0018] The hexagonal boron nitride powder and the binder powder are heated and pressurized to a temperature of 1900° C. to 2400° C. and a pressure of 8 GPa or more at a temperature and pressure within the stable region of wurtzite boron nitride.
[0019] The stable region of wurtzite boron nitride is a region that satisfies the following equation 1 and the following equation 2 simultaneously when the temperature is set to T°C and the pressure is set to PGPa.
[0020] Formula 1: P ≥ -0.0037T + 11.301
[0021] Formula 2: P≤-0.085T+117
[0022] In the heating and pressurizing step, the penetration temperature into the stable region of the wurtzite boron nitride is 600° C. or higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the pressure-temperature phase diagram of boron nitride.
[0024] Figure 2 This is a diagram for explaining a method for producing a cubic boron nitride polycrystal according to one embodiment of the present disclosure (scheme A).
[0025] Figure 3 It is a diagram for explaining a method for producing a cubic boron nitride polycrystal according to another embodiment of the present disclosure (scheme B).
[0026] Figure 4 This is a diagram for explaining a conventional example of a method for producing a cubic boron nitride polycrystal.
[0027] Figure 5This is a diagram for explaining a reference example of a method for producing a cubic boron nitride polycrystal.
[0028] Figure 6 This is a diagram showing a flow chart of a method for producing a cubic boron nitride sintered body according to one embodiment of the present disclosure. DETAILED DESCRIPTION
[0029] [Problems to be Solved by the Present Disclosure]
[0030] In recent years, in the automobile industry, in order to achieve both high performance and light weight of automobiles, the use of cast iron materials that are high-strength even in thin walls has increased.
[0031] As cast iron materials, flake graphite cast iron (hereinafter also referred to as "gray cast iron") is generally used. In recent years, among flake graphite cast irons, there is a tendency to use FC300 and the like having a higher tensile strength than FC200. In addition, the use ratio of vermicular graphite cast iron and ductile iron, etc., which have higher strength than flake graphite cast iron, has also increased. Furthermore, among ductile cast irons, there is a tendency to use FCD600 and FCD700 having a higher tensile strength than FCD450.
[0032] In addition to the above-mentioned material changes, the trend of increasing expectations for high-efficiency machining in order to improve productivity is also accelerating. That is, in high-efficiency machining of high-strength cast iron materials, tools that can have a long tool life are also required.
[0033] Therefore, an object of the present invention is to provide a cubic boron nitride sintered body which, when used as a tool material, can extend the life of the tool even in high-efficiency machining of a high-strength cast iron material.
[0034] [Effects of the present disclosure]
[0035] When the cubic boron nitride sintered body of the present disclosure is used as a tool material, it is possible to extend the life of the tool even in high-efficiency machining of high-strength cast iron materials.
[0036] [Overview of Embodiments]
[0037] First, embodiments of the present disclosure will be described by way of examples.
[0038] (1) The cubic boron nitride sintered body disclosed in the present invention comprises 40% by volume or more and 96% by volume or less of cubic boron nitride particles and 4% by volume or more and 60% by volume or less of a binding phase, wherein:
[0039] The dislocation density of the cubic boron nitride particles is less than 1×10 15 / m 2 .
[0040] When the cubic boron nitride sintered body of the present disclosure is used as a tool material, it is possible to extend the life of the tool even in high-efficiency machining of high-strength cast iron materials.
[0041] (2) Preferably, the bonding phase comprises at least one selected from the group consisting of a simple substance, an alloy, and an intermetallic compound, wherein the simple substance, the alloy, and the intermetallic compound are selected from the group consisting of elements of Group IV, Group V, and Group VI of the periodic table, aluminum, silicon, cobalt, and nickel, or,
[0042] The binding phase comprises at least one selected from the group consisting of compounds and solid solutions derived from the compounds, wherein the compound is composed of at least one element selected from the group consisting of Group IV elements, Group V elements, Group VI elements, aluminum, silicon, cobalt and nickel of the periodic table and at least one element selected from the group consisting of nitrogen, carbon, boron and oxygen, or,
[0043] The bonding phase includes at least one selected from the group consisting of a simple substance, an alloy, and an intermetallic compound, wherein the simple substance, the alloy, and the intermetallic compound are selected from the group consisting of elements of Group IV, Group V, and Group VI of the periodic table, aluminum, silicon, cobalt, and nickel, and the bonding phase includes at least one selected from the group consisting of compounds and solid solutions derived from the compounds, wherein the compounds are composed of at least one element selected from the group consisting of elements of Group IV, Group V, and Group VI of the periodic table, aluminum, silicon, cobalt, and nickel, and at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen.
[0044] As a result, the tool life becomes longer.
[0045] (3) The method for producing a cubic boron nitride sintered body disclosed in the present invention is the method for producing a cubic boron nitride sintered body described above, wherein:
[0046] The method for producing a cubic boron nitride sintered body comprises:
[0047] A process of preparing hexagonal boron nitride powder and bonding material powder; and
[0048] The hexagonal boron nitride powder and the binder powder are heated and pressurized to a temperature of 1900° C. to 2400° C. and a pressure of 8 GPa or more at a temperature and pressure within the stable region of wurtzite boron nitride.
[0049] The stable region of wurtzite boron nitride is a region that satisfies the following equation 1 and the following equation 2 simultaneously when the temperature is set to T°C and the pressure is set to PGPa.
[0050] Formula 1: P ≥ -0.0037T + 11.301
[0051] Formula 2: P≤-0.085T+117
[0052] In the heating and pressurizing step, the penetration temperature into the stable region of the wurtzite boron nitride is 600° C. or higher.
[0053] Thereby, it is possible to obtain a cubic boron nitride sintered body which, when used as a tool material, can extend the life of the tool even in highly efficient machining of high-strength cast iron materials.
[0054] [Details of implementation method]
[0055] The inventors of the present invention first observed the damage state of the tool when the tool using the conventional cubic boron nitride sintered body was used for high-efficiency machining of high-strength cast iron materials, and studied the cause thereof. As a result, it was newly discovered that, because the thermal conductivity of the cubic boron nitride sintered body is insufficient, the temperature near the contact point with the cut material rises, and the flank wear is likely to be aggravated, especially when the tool is used for high-efficiency machining of high-strength cast iron materials.
[0056] The inventors of the present invention have conducted a more detailed study on the factors affecting the thermal conductivity of cubic boron nitride sintered bodies. As a result, the inventors of the present invention have newly discovered that the dislocation density of cubic boron nitride particles affects the thermal conductivity of cubic boron nitride sintered bodies and is closely related to tool life.
[0057] As a result of intensive studies conducted by the inventors of the present invention based on the above findings, the inventors have completed the cubic boron nitride sintered body and the method for producing the same disclosed herein.
[0058] Hereinafter, in the present specification describing the specific examples of the cubic boron nitride sintered body and the method for producing the same disclosed herein, when a compound is represented by a chemical formula, when the atomic ratio is not particularly limited, all conventionally known atomic ratios are included, and the atomic ratios are not necessarily limited to the atomic ratios within the stoichiometric range. For example, when "TiC" is described, the ratio of the number of atoms constituting TiC includes all conventionally known atomic ratios.
[0059] 《Implementation 1: Cubic boron nitride sintered body》
[0060] The cubic boron nitride sintered body according to one embodiment of the present disclosure is a cubic boron nitride sintered body comprising 40 volume % or more and 96 volume % or less of cubic boron nitride particles and 4 volume % or more and 60 volume % or less of a binding phase, wherein the dislocation density of the cubic boron nitride particles is less than 1×10 15 / m 2 .
[0061] When the cubic boron nitride sintered body of the present disclosure is used as a tool material, it is possible to extend the tool life, especially in the high-efficiency machining of high-strength cast iron materials. The reasons for this are presumably as described below (i) and (ii).
[0062] (i) The cubic boron nitride sintered body of the present disclosure contains 40% by volume or more and 96% by volume or less of cBN particles having high hardness, strength and toughness. Therefore, it is estimated that the cubic boron nitride sintered body has excellent wear resistance and defect resistance, and the tool life is prolonged.
[0063] (ii) In the cubic boron nitride sintered body of the present invention, the dislocation density of the cubic boron nitride particles is less than 1×10 15 / m 2 The thermal conductivity of the cubic boron nitride particles is improved. Therefore, the thermal conductivity of the cubic boron nitride sintered body containing the cubic boron nitride particles is also improved. Therefore, it is estimated that even when a tool using the cubic boron nitride sintered body is used for high-efficiency processing of high-strength cast iron materials, the temperature near the contact point with the cut material is not easy to rise, the crater wear is suppressed, and the tool life is prolonged.
[0064] In addition, in the above description, the case where the tool using the cubic boron nitride sintered body of the present disclosure has a long tool life in the high-efficiency processing of high-strength cast iron materials is described, but the cut material is not limited to this. Examples of the cut material include chrome-molybdenum steel (SCM415), carbon steel for mechanical structures (S50C), high-carbon chromium bearing steel (SUJ2, SUJ4), alloy tool steel (SKD11), etc.
[0065] (Composition of cubic boron nitride sintered body)
[0066] The cubic boron nitride sintered body of the present disclosure comprises 40% to 96% by volume of cubic boron nitride particles and 4% to 60% by volume of a binder phase. The cBN sintered body may contain unavoidable impurities caused by raw materials, production conditions, and the like.
[0067] The lower limit of the content ratio of cBN particles in the cBN sintered body is 40% by volume or more, and more preferably 45% by volume or more. The upper limit of the content ratio of cBN particles in the cBN sintered body is 96% by volume or less, and more preferably 90% by volume or less. The content ratio of cBN particles in the cBN sintered body is 40% by volume or more and 96% by volume or less, and more preferably 45% by volume or more and 90% by volume or less.
[0068] The lower limit of the content ratio of the binder phase in the cBN sintered body is 4% by volume or more, and more preferably 10% by volume or more. The upper limit of the content ratio of the binder phase in the cBN sintered body is 60% by volume or less, and more preferably 55% by volume or less. The content ratio of the binder phase in the cBN sintered body is 4% by volume or more and 60% by volume or less, and preferably 10% by volume or more and 55% by volume or less.
[0069] The content ratio (volume %) of cBN particles in the cBN sintered body and the content ratio (volume %) of the binder phase can be confirmed by using an energy dispersive X-ray analyzer (EDX) (Octane Eelect EDS system) (hereinafter also referred to as "SEM-EDX") attached to a scanning electron microscope (SEM) ("JSM-7800F" (trade name) manufactured by JEOL Ltd.) to observe the structure of the cBN sintered body, perform elemental analysis, etc. The specific measurement method is as follows.
[0070] First, cut any position of the cBN sintered body to prepare a sample containing a cross section of the cBN sintered body. In the preparation of the cross section, a focused ion beam device, a cross section polishing device, etc. can be used. Then, the above cross section is observed at 5000 times using a SEM to obtain a reflected electron image. In the reflected electron image, the area where the cBN particles exist is a black area, and the area where the bonding phase exists is a gray area or a white area.
[0071] Next, the reflected electron image was binarized using image analysis software ("WinROOF" from Mitani Shoji Co., Ltd.). Based on the binarized image, the area ratio of pixels originating from the dark field (pixels originating from cBN particles) in the area of the measured field of view was calculated. By considering the calculated area ratio as volume %, the content ratio (volume %) of cBN particles can be calculated.
[0072] The content ratio (volume %) of the binder phase can be determined by calculating the area ratio of pixels derived from the bright field (pixels derived from the binder phase) in the area of the measurement field from the binarized image.
[0073] Within the scope of the applicant's measurements, it was confirmed that as long as the content ratio (volume %) of cBN particles in the cBN sintered body and the content ratio (volume %) of the binding phase were measured in the same sample, there was almost no deviation in the measurement results even if the selected part of the measurement field of view was changed and multiple calculations were performed, and the measurement results would not change arbitrarily even if the measurement field of view was arbitrarily set.
[0074] Furthermore, it can be confirmed that the pixels derived from the dark field are derived from the cBN particles by performing elemental analysis on the cBN sintered body using SEM-EDX.
[0075] (Unavoidable impurities)
[0076] The cubic boron nitride sintered body of the present invention may contain inevitable impurities within the scope of showing the effect of the present invention. As inevitable impurities, for example, hydrogen, oxygen, and carbon can be listed. In the case where the cubic boron nitride sintered body contains inevitable impurities, the content of inevitable impurities is preferably less than 0.1 mass %. The content of inevitable impurities can be measured by secondary ion mass spectrometry (SIMS).
[0077] 《Cubic Boron Nitride Granules》
[0078] (Dislocation density)
[0079] The dislocation density of the cubic boron nitride particles contained in the cubic boron nitride sintered body of the present invention is less than 1×10 15 / m 2 . The cubic boron nitride particles have a higher thermal conductivity than conventional cubic boron nitride particles. Therefore, the thermal conductivity of the cubic boron nitride sintered body containing the cubic boron nitride particles is also improved. Therefore, it is inferred that even when the tool using the cubic boron nitride sintered body is used for high-efficiency processing of high-strength cast iron materials, the temperature near the contact point with the cut material is not easy to rise, the flank wear is suppressed, and the tool life is prolonged.
[0080] The upper limit of dislocation density of cubic boron nitride particles is less than 1×10 15 / m 2 , preferably 9.0×10 14 / m 2 Below, more preferably 8.0×10 14 / m 2 The lower limit of the dislocation density is not particularly limited, but from the perspective of production, it is 1×10 14 / m 2 above.
[0081] In this specification, the dislocation density of cubic boron nitride particles is measured in a large-scale radiation light facility (for example, SPring-8 (Hyogo Prefecture)). Specifically, the measurement is performed by the following method.
[0082] The cubic boron nitride sintered body sample was immersed in 140°C fluorinated nitric acid (hydrofluoric acid: nitric acid = 5:5 (volume ratio)) in a sealed container for 48 hours. Thus, the binder phase was completely dissolved in the fluorinated nitric acid, leaving only cBN particles. The cBN particles were filled in a 0.3 mmΦ capillary tube for X-ray crystal analysis manufactured by TOHO ("Mark Tube" manufactured by TOHO) as a sealed test body.
[0083] X-ray diffraction measurement was performed on the test body under the following conditions to obtain line profiles of diffraction peaks from various planes, which are the main orientations of cubic boron nitride: (111), (200), (220), (311), (400), and (531).
[0084] (X-ray diffraction measurement conditions)
[0085] X-ray source: radiation
[0086] Device conditions: Detector MYTHEN
[0087] Energy: 18keV (wavelength: )
[0088] Camera length: 573mm
[0089] Peaks measured: (111), (200), (220), (311), (400), and (531) of cubic boron nitride. If the outline is difficult to obtain due to texture or orientation, the peak of the surface index is excluded.
[0090] Measurement conditions: The measurement points are set to 9 or more points in the full width at half maximum corresponding to each measurement peak. The peak top intensity is 2000 counts or more. Since the edge of the peak is also used for analysis, the measurement range is about 10 times the full width at half maximum.
[0091] The line profile obtained by the above-mentioned X-ray diffraction measurement becomes a shape that includes both the real expansion caused by physical quantities such as the inhomogeneous strain of the sample and the expansion caused by the device. In order to obtain the inhomogeneous strain and the crystallite size, the components caused by the device are removed from the measured line profile to obtain the real line profile. The real line profile is obtained by fitting the obtained line profile and the line profile caused by the device using the pseudo-Voigt function and subtracting the line profile caused by the device. As a standard sample for removing the diffraction line expansion caused by the device, LaB 6 In addition, when using radiated light with a high degree of parallelism, the diffraction line spread caused by the device can also be regarded as zero.
[0092] The obtained true line profile is analyzed using the modified Williamson-Hall method and the modified Warren-Averbach method to calculate the dislocation density. The modified Williamson-Hall method and the modified Warren-Averbach method are known line profile analysis methods for obtaining the dislocation density.
[0093] The modified Williamson-Hall method is represented by the following formula (I).
[0094]
Number 1
[0095]
[0096] (In the above formula (I), ΔK represents the half-value width of the line profile, D represents the crystallite size, M represents the configuration parameter, b represents the Burgers vector, ρ represents the dislocation density, K represents the scattering vector, O(K 2 C) represents K 2 The higher-order terms of C, C represents the average value of the contrast factor).
[0097] C in the above formula (I) is represented by the following formula (II).
[0098] C=C h00 [1-q(h 2 k 2 +h 2 l 2 +k 2 l 2 ) / (h 2 +k 2 +l 2 ) 2 ] (II)
[0099] In the above formula (II), the contrast factors C of screw dislocation and edge dislocation are h00 The coefficient q related to the contrast factor is calculated using the code ANIZC, with the slip system as <110> {111}, elastic stiffness C 11 8.44GPa, C 12 1.9GPa, C 44 The contrast factor C is calculated as 4.83 GPa. h00 The ratio of screw dislocations is 0.203 and that of edge dislocations is 0.212. The coefficient q related to the contrast factor is 1.65 for screw dislocations and 0.58 for edge dislocations. In addition, the ratio of screw dislocations is fixed at 0.5 and that of edge dislocations is fixed at 0.5.
[0100] In addition, the contrast factor C is used to establish the relationship of the following formula (III) between dislocation and inhomogeneous strain.
[0101] <ε(L) 2 >=(ρCb 2 / 4π)ln(R e / L) (III)
[0102] (In the above formula (III), R e represents the effective radius of the dislocation. )
[0103] The relationship of the above formula (III) and the Warren-Averbach formula can be expressed as the following formula (IV), and the dislocation density ρ and the crystallite size can be obtained as a modified Warren-Averbach method.
[0104] lnA(L)=lnA S (L)-(πL 2 ρb 2 / 2)ln(R e / L)(K 2 C)+O(K 2 C) 2 (IV)
[0105] (In the above formula (IV), A(L) represents the Fourier series, A S (L) represents the Fourier series related to the crystallite size, and L represents the Fourier length. )
[0106] The details of the modified Williamson-Hall method and the modified Warren-Averbach method are described in “T. Ungar and A. Borbely, “The effect of dislocation contrast on x-ray linebroadening: A new approach to line profile analysis” Appl. Phys. Lett., vol. 69, no. 21, p. 3173, 1996.” and “T. Ungar, S. Ott, P. Sanders, A. Borbely, J. Weertman, “Dislocations, grain size and planar faults in nanostructured copper determined by high resolution X-ray diffraction and a new procedure of peak profile analysis” Acta Mater., vol. 46, no. 10, pp. 3693-3699, 1998.”
[0107] In the range of measurement performed by the applicant, it was confirmed that as long as the dislocation density of cBN particles is measured in the same sample, there is almost no deviation in the measurement results even if the selected part of the measurement range is changed and calculations are performed multiple times, and the measurement field does not change arbitrarily even if the measurement field is set arbitrarily.
[0108] "Combination Phase"
[0109] In the cBN sintered body of the present disclosure,
[0110] The bonding phase includes at least one selected from the group consisting of a simple substance, an alloy, and an intermetallic compound, wherein the simple substance, the alloy, and the intermetallic compound are selected from the group consisting of Group IV elements, Group V elements, Group VI elements, aluminum, silicon, cobalt, and nickel of the periodic table (hereinafter also referred to as "Group A"), or
[0111] The binding phase comprises at least one selected from the group consisting of compounds and solid solutions derived from the compounds, wherein the compound is composed of at least one element selected from the group consisting of Group IV elements, Group V elements, Group VI elements, aluminum, silicon, cobalt and nickel (Group A) of the periodic table and at least one element selected from the group consisting of nitrogen, carbon, boron and oxygen (hereinafter also referred to as "Group B"), or,
[0112] The binding phase includes at least one selected from the group consisting of a simple substance, an alloy, and an intermetallic compound, wherein the simple substance, the alloy, and the intermetallic compound are selected from the group consisting of Group IV elements, Group V elements, Group VI elements, aluminum, silicon, cobalt, and nickel (Group A) of the periodic table, and the binding phase includes at least one selected from the group consisting of a compound and a solid solution derived from the compound, wherein the compound is composed of at least one element selected from the group consisting of Group IV elements, Group V elements, Group VI elements, aluminum, silicon, cobalt, and nickel (Group A) of the periodic table and at least one element selected from the group consisting of nitrogen, carbon, boron, and oxygen (Group B). That is, the binding phase may be in any of the following forms (a) to (f).
[0113] (a) It is composed of at least one of a simple substance, an alloy, and an intermetallic compound of group A.
[0114] (b) Containing at least one of the simple substance, alloy, and intermetallic compound of group A.
[0115] (c) It is composed of at least one selected from the group consisting of compounds and solid solutions derived from the compounds, wherein the compounds are composed of at least one element selected from Group A and at least one element selected from Group B.
[0116] (d) contains at least one selected from the group consisting of a compound and a solid solution derived from the compound, wherein the compound consists of at least one element selected from Group A and at least one element selected from Group B.
[0117] (e) It is composed of at least one of the simple substances, alloys, and intermetallic compounds of group A, and at least one of the group consisting of compounds and solid solutions derived from the compounds, wherein the compounds are composed of at least one element selected from group A and at least one element selected from group B.
[0118] (f) at least one of a simple substance, an alloy, an intermetallic compound of group A, and at least one of a group consisting of compounds and solid solutions derived from said compounds, wherein said compound consists of at least one element selected from group A and at least one element selected from group B.
[0119] The binder phase has a lower reactivity with iron than cBN, so it plays a role in suppressing chemical wear and thermal wear during cutting of high-strength cast iron materials. That is, if the cBN sintered body contains a binder phase, the wear resistance in high-efficiency machining of high-strength cast iron materials is improved.
[0120] The fourth group elements of the periodic table include titanium (Ti), zirconium (Zr) and hafnium (Hf). The fifth group elements include vanadium (V), niobium (Nb) and tantalum (Ta). The sixth group elements include chromium (Cr), molybdenum (Mo) and tungsten (W). Hereinafter, the fourth group elements, the fifth group elements, the sixth group elements, aluminum, silicon, cobalt and nickel are also referred to as "first metal elements".
[0121] Examples of alloys of the first metal element include Ti-Zr, Ti-Hf, Ti-V, Ti-Nb, Ti-Ta, Ti-Cr, and Ti-Mo. Examples of intermetallic compounds of the first metal element include TiCr 2 、Ti 3 Al, Co-Al.
[0122] Examples of the compound (nitride) containing the first metal element and nitrogen include titanium nitride (TiN), zirconium nitride (ZrN), hafnium nitride (HfN), vanadium nitride (VN), niobium nitride (NbN), tantalum nitride (TaN), chromium nitride (CrN), and the like. 2 N), molybdenum nitride (MoN), tungsten nitride (WN), aluminum nitride (AlN), silicon nitride (Si 3 N 4 ), cobalt nitride (CoN), nickel nitride (NiN), titanium zirconium nitride (TiZrN), titanium hafnium nitride (TiHfN), titanium vanadium nitride (TiVN), titanium niobium nitride (TiNbN), titanium tantalum nitride (TiTaN), titanium chromium nitride (TiCrN), titanium molybdenum nitride (TiMoN), titanium tungsten nitride (TiWN), titanium aluminum nitride (TiAlN, Ti 2 AlN、Ti 3AlN), zirconium hafnium nitride (ZrHfN), zirconium vanadium nitride (ZrVN), zirconium niobium nitride (ZrNbN), zirconium tantalum nitride (ZrTaN), zirconium chromium nitride (ZrCrN), zirconium molybdenum nitride (ZrMoN), zirconium tungsten nitride (ZrWN), hafnium vanadium nitride (HfVN), hafnium niobium nitride (HfNbN), hafnium tantalum nitride (HfTaN), hafnium chromium nitride (HfCrN), hafnium molybdenum nitride (HfMoN), hafnium tungsten nitride (HfWN), vanadium niobium nitride (V The following are some of the most common nitrides used in the chemical industry: NbN), vanadium tantalum nitride (VTaN), vanadium chromium nitride (VCrN), vanadium molybdenum nitride (VMoN), vanadium tungsten nitride (VWN), tantalum nitride (NbTaN), niobium chromium nitride (NbCrN), niobium molybdenum nitride (NbMoN), niobium tungsten nitride (NbWN), tantalum chromium nitride (TaCrN), tantalum molybdenum nitride (TaMoN), tantalum tungsten nitride (TaWN), chromium molybdenum nitride (CrMoN), chromium tungsten nitride (CrWN), and molybdenum tungsten nitride (MoWN).
[0123] Examples of the compound (carbide) containing the first metal element and carbon include titanium carbide (TiC), zirconium carbide (ZrC), hafnium carbide (HfC), vanadium carbide (VC), niobium carbide (NbC), tantalum carbide (TaC), chromium carbide (Cr 3 C 2 ), molybdenum carbide (MoC), tungsten carbide (WC), silicon carbide (SiC), tungsten cobalt carbide (W 2 Co 3 C).
[0124] Examples of the compound (boride) containing the first metal element and boron include titanium boride (TiB 2 ), zirconium boride (ZrB 2 ), Hafnium Boride (HfB 2 ), vanadium boride (VB 2 ), niobium boride (NbB 2 ), Tantalum boride (TaB 2 ), chromium boride (CrB), molybdenum boride (MoB), tungsten boride (WB), aluminum boride (AlB 2 ), cobalt boride (Co 2 B), nickel boride (Ni 2 B).
[0125] Examples of the compound (oxide) containing the first metal element and oxygen include titanium oxide (TiO 2 ), zirconium oxide (ZrO 2 ), hafnium oxide (HfO 2 ), vanadium oxide (V 2 O 5 ), niobium oxide (Nb 2 O5 ), Tantalum Oxide (Ta 2 O 5 ), chromium oxide (Cr 2 O 3 ), molybdenum oxide (MoO 3 ), tungsten oxide (WO 3 ), aluminum oxide (Al 2 O 3 ), silicon oxide (SiO 2 ), cobalt oxide (CoO), and nickel oxide (NiO).
[0126] As compounds (carbonitrides) containing the above-mentioned first metal element, carbon and nitrogen, for example, titanium carbonitride (TiCN), zirconium carbonitride (ZrCN), hafnium carbonitride (HfCN), titanium niobium carbonitride (TiNbCN), titanium zirconium carbonitride (TiZrCN), titanium tantalum carbonitride (TiTaCN), titanium hafnium carbonitride (TiHfCN), and titanium chromium carbonitride (TiCrCN) can be listed.
[0127] As compounds (nitride oxides) composed of the above-mentioned first metal element, oxygen and nitrogen, for example, titanium oxynitride (TiON), zirconium oxynitride (ZrON), hafnium oxynitride (HfON), vanadium oxynitride (VON), niobium oxynitride (NbON), tantalum oxynitride (TaON), chromium oxynitride (CrON), molybdenum oxynitride (MoON), tungsten oxynitride (WON), aluminum oxynitride (AlON), and silicon aluminum oxynitride (SiAlON) can be listed.
[0128] The solid solution derived from the above-mentioned compounds refers to a state in which two or more of these compounds are dissolved in each other's crystal structures, and refers to an intrusive solid solution or a substitutional solid solution.
[0129] The above compounds may be used alone or in combination of two or more.
[0130] The total content of the compound and the solid solution derived from the compound in the binder phase is measured by the RIR method (Reference Intensity Ratio) based on XRD.
[0131] The binder phase may contain other components in addition to the above-mentioned compounds. Examples of elements constituting other components include manganese (Mn) and rhenium (Re).
[0132] The composition of the binder phase included in the cBN sintered body can be determined by XRD (X-ray Diffraction).
[0133] <Purpose>
[0134] The cubic boron nitride sintered body disclosed in the present invention is preferably used for cutting tools, wear-resistant tools, grinding tools, and the like.
[0135] The cutting tool, wear-resistant tool and grinding tool using the cubic boron nitride sintered body disclosed in the present invention may be composed of the cubic boron nitride sintered body in its entirety or may be composed of only a portion thereof (e.g., the blade tip portion in the case of a cutting tool). Furthermore, a coating film may be formed on the surface of each tool.
[0136] Examples of cutting tools include drills, end mills, replaceable cutting inserts for drills, replaceable cutting inserts for end mills, replaceable cutting inserts for milling, replaceable cutting inserts for turning, metalworking saws, gear cutting tools, reamers, taps, cutting tools, and the like.
[0137] Examples of wear-resistant tools include punches, scribers, scribing wheels, dressers, etc. Examples of grinding tools include grinding wheels, etc.
[0138] 《Implementation 2: Method for producing a cubic boron nitride sintered body》
[0139] use Figure 1 to Figure 5 A method for producing a cubic boron nitride sintered body according to an embodiment of the present disclosure will be described. Figure 1 is the pressure-temperature phase diagram of boron nitride. Figure 2 , Figure 3 It is a diagram for explaining a method for producing a cubic boron nitride sintered body according to one embodiment of the present disclosure. Figure 4 This is a diagram for explaining a conventional example of a method for producing a cubic boron nitride sintered body. Figure 5 It is a diagram for explaining a reference example of a method for producing a cubic boron nitride sintered body. Figure 6 This is a diagram showing a flow chart of a method for producing a cubic boron nitride sintered body according to one embodiment of the present disclosure.
[0140] The method for producing a cubic boron nitride sintered body according to the present embodiment is a method for producing a cubic boron nitride sintered body according to the first embodiment, and comprises a step of preparing hexagonal boron nitride powder (hereinafter, also referred to as "hBN powder") and a bonding material powder (hereinafter, also referred to as "preparation step"). Figure 6 ) and a step of heating and pressurizing the hexagonal boron nitride powder and the binder powder to a temperature of 1900°C to 2400°C and a pressure of 8 GPa or more at a temperature and pressure within the stable region of wurtzite boron nitride (hereinafter also referred to as a "heating and pressurizing step"). Figure 6The stable region of wurtzite boron nitride is the region that satisfies the following equations 1 and 2 simultaneously when the temperature is set to T°C and the pressure is set to PGPa.
[0141] Formula 1: P ≥ -0.0037T + 11.301
[0142] Formula 2: P≤-0.085T+117
[0143] In the above-mentioned heating and pressing step, the penetration temperature into the stable region of wurtzite boron nitride is 600° C. or higher.
[0144] The method for producing a cubic boron nitride sintered body according to the present embodiment may include a step of pressurizing the hexagonal boron nitride powder to a pressure of 0.5 GPa to 6 GPa while maintaining the temperature in a range of -50°C to 100°C before the heating and pressurizing step (hereinafter also referred to as a "pre-treatment step"). Figure 6 Indicated by S2.)
[0145] The method for producing a cubic boron nitride sintered body according to the present embodiment may include a step of maintaining the cubic boron nitride sintered body obtained by the heating and pressing step at a temperature of 1900° C. to 2400° C. and a pressure of 8 GPa or more for 10 minutes or more after the heating and pressing step (hereinafter also referred to as a “temperature and pressure maintaining step”). Figure 6 Indicated by S4.)
[0146] Before describing in detail the method for producing a cubic boron nitride sintered body according to the present embodiment, conventional examples and reference examples of the method for producing a cubic boron nitride sintered body will be described to facilitate understanding.
[0147] like Figure 1 As shown, there are three phases in boron nitride: hexagonal boron nitride, which is a stable phase at room temperature and pressure; cubic boron nitride, which is a stable phase at high temperature and high pressure; and wurtzite boron nitride, which is a quasi-stable phase between the transition from hexagonal boron nitride to cubic boron nitride.
[0148] The boundary of each phase can be expressed by a linear function. In this specification, the temperature and pressure in the stable region of each phase can be expressed by a linear function.
[0149] In this specification, the temperature and pressure within the stable region of wurtzite boron nitride (in Figure 1 The "wBN stable region" is defined as the temperature and pressure that simultaneously satisfy the following equations 1 and 2 when the temperature is T°C and the pressure is PGPa.
[0150] Formula 1: P ≥ -0.0037T + 11.301
[0151] Formula 2: P≤-0.085T+117
[0152] In this specification, the temperature and pressure within the stable region of hexagonal boron nitride (in Figure 1 The “hBN stable region” is defined as the temperature and pressure that simultaneously satisfy the following equations A and B when the temperature is set to T°C and the pressure is set to PGPa, or the temperature and pressure that simultaneously satisfy the following equations C and D.
[0153] Formula A: P≤-0.0037T+11.301
[0154] Formula B: P≤-0.085T+117
[0155] Formula C: P≤0.0027T+0.3333
[0156] Formula D: P ≥ -0.085T + 117
[0157] In this specification, the temperature and pressure within the stable region of cubic boron nitride (in Figure 1 The "cBN stable region" is defined as the temperature and pressure that simultaneously satisfy the following equations D and E when the temperature is T°C and the pressure is PGPa.
[0158] Formula D: P ≥ -0.085T + 117
[0159] Formula E: P ≥ 0.0027T + 0.3333
[0160] In the manufacturing method according to the present embodiment, hexagonal boron nitride powder and binder powder are heated and pressurized to a temperature of 1900° C. to 2400° C. and a pressure of 8 GPa or more at a temperature and pressure within the stable region of wurtzite boron nitride. This temperature and pressure are the temperature and pressure at which cubic boron nitride having excellent tool performance can be obtained.
[0161] In the past, as a path for making hexagonal boron nitride reach a temperature (above 1900°C and below 2400°C) and a pressure (above 8 GPa) within the stable region of cubic boron nitride, which can produce cubic boron nitride with excellent tool performance, research has been conducted. Figure 4 The path shown (hereinafter, also referred to as " Figure 4 path”).
[0162] exist Figure 4In the path, from the starting temperature and starting pressure (normal temperature and pressure), the pressure is increased to the pressure in the stable region of cubic boron nitride (for example, 10 GPa or more) ( Figure 4 Then, the temperature is raised to a temperature within the stable region of cubic boron nitride (for example, above 1900° C.) ( Figure 4 Arrow E2). Figure 4 In the path, heating and pressurizing are performed once each, so the control of the heating and pressurizing operation is simple and has been adopted in the past.
[0163] However, in Figure 4 In the path, the penetration temperature into the stable region of wurtzite boron nitride is less than 600°C, and it is difficult to cause atomic diffusion. The phase transition from hexagonal boron nitride to wurtzite boron nitride is mainly a diffusionless phase transition. Therefore, in the obtained cubic boron nitride sintered body, lattice defects and coarse particles are likely to exist. Therefore, the cubic boron nitride has a tendency to easily produce sudden defects during processing, which shortens the tool life.
[0164] On the other hand, in order to facilitate atomic diffusion, it is also possible to consider increasing the phase transition temperature. Figure 5 In the path, starting from the starting temperature and starting pressure (normal temperature and pressure), the temperature (e.g., 1500°C) and pressure (e.g., 9 GPa) within the stable region of cubic boron nitride are heated and pressurized in a manner that does not pass through the stable region of wurtzite boron nitride ( Figure 5 Then, the temperature is further increased (for example, to 2100°C) ( Figure 5 arrow F4).
[0165] exist Figure 5 In the path of , hexagonal boron nitride directly changes into cubic boron nitride, but since the crystal structures of hexagonal boron nitride and cubic boron nitride are very different, lattice defects are easily generated during the phase change. Therefore, the cubic boron nitride has a tendency to shorten the tool life. Furthermore, since the crystal structures of hexagonal boron nitride and cubic boron nitride are very different, the conversion rate to cubic boron nitride is less than 98.5% by volume. Therefore, the performance of the tool using the obtained cubic boron nitride sintered body is reduced.
[0166] As described above, in the temperature and pressure paths studied in the past, it is difficult to suppress the generation of lattice defects, and it is impossible to produce cubic boron nitride sintered bodies with excellent tool life. In view of this situation, the applicant has conducted in-depth research on the pressure and temperature paths, and found that by treating hexagonal boron nitride and binder powders under the temperature and pressure conditions specified in the above-mentioned heating and pressurizing process, the generation of lattice defects in the sintered body can be suppressed, and a cubic boron nitride sintered body with a long tool life can be obtained even in the high-efficiency processing of high-strength cast iron materials. Figure 2 , Figure 3 The details of each step of the production method according to the present embodiment will be described.
[0167] <Preparation process>
[0168] As raw materials for the cubic boron nitride sintered body, hexagonal boron nitride powder (hereinafter also referred to as "hBN powder") and a binder phase powder are prepared. The purity of the hexagonal boron nitride powder (the content ratio of hexagonal boron nitride) is preferably 98.5% or more, more preferably 99% or more, and most preferably 100%. The particle size of the hexagonal boron nitride powder is not particularly limited, and can be, for example, 0.1 μm or more and 10 μm or less.
[0169] The binder powder refers to a raw material powder of a binder phase contained in a cBN sintered body. As the binder powder, a powder containing at least one selected from the group consisting of a simple substance, an alloy, and an intermetallic compound can be used, wherein the simple substance, the alloy, and the intermetallic compound are selected from the group consisting of Group IV elements, Group V elements, Group VI elements, aluminum, silicon, cobalt, and nickel in the periodic table. When two or more binder powders are used, each binder powder is weighed so as to achieve a predetermined mixing ratio.
[0170] Next, the binder powder is mixed and crushed. There is no particular limitation on the mixing and crushing method. From the perspective of efficient and homogeneous mixing, mixing and crushing using a medium such as a ball, and mixing and crushing using a jet mill are preferred. Each mixing and crushing method may be a wet method or a dry method.
[0171] The hBN powder prepared above and the binder powder are mixed using a wet ball mill using ethanol, acetone, etc. as a solvent to prepare a mixed powder. The mixing ratio of the hexagonal boron nitride powder and the binder powder is adjusted so that the proportion of the cubic boron nitride particles in the finally obtained cubic boron nitride sintered body is 40% by volume or more and 96% by volume or less. The solvent is removed by natural drying after mixing. Thereafter, impurities such as moisture adsorbed on the surface of the mixed powder are volatilized by heat treatment, so that the surface of the mixed powder is cleaned.
[0172] <Pre-treatment process>
[0173] Next, the mixed powder is pressurized to a pressure of 0.5 GPa to 6 GPa using an ultra-high pressure and high temperature generator while maintaining the temperature in the range of -50°C to 100°C ( Figure 2 Arrow A1, Figure 3 .
[0174] By performing the pretreatment process, the gaps between the mixed powders can be compressed and unnecessary gas in the mixed powders can be discharged outside the system, thereby preventing the quality degradation caused by the chemical reaction between the gas and the mixed powders.
[0175] By performing the pretreatment step, the density of the mixed powder can be increased to a level where the outer shape hardly changes even if further pressurization is performed. In this state, the heating and pressurization step can be performed, so stable production is possible.
[0176] The temperature in the pretreatment step is preferably maintained in the range of -50°C to 100°C, more preferably 0°C to 50°C. The ultimate pressure in the pretreatment step is preferably 0.5 GPa to 5 GPa, more preferably 1 GPa to 3 GPa.
[0177] In the method for producing a cubic boron nitride sintered body according to the present embodiment, the pretreatment step is an optional step. Therefore, after the above-mentioned preparation step, the heating and pressing step described later may be performed without performing the pretreatment step.
[0178] <Heating and Pressurizing Process>
[0179] Next, the mixed powder is heated and pressurized to a temperature of 1900° C. to 2400° C. and a pressure of 8 GPa or more at a temperature and pressure within the stable region of wurtzite boron nitride. Figure 2 Arrows A2, A3 and A4 are shown in Figure 3 In the figure, there are arrows B2, B3 and B4.) In the heating and pressing step, the penetration temperature into the stable region of wurtzite boron nitride is 600°C or higher.
[0180] In this specification, the penetration temperature into the stable region of wurtzite boron nitride refers to the temperature at the time point when the wurtzite boron nitride first reaches the stable region in the heating and pressing process. Figure 2 The temperature at the intersection of arrow A3 and the line P = -0.0037T + 11.301 (about 1200°C) is shown in Figure 3The middle is the temperature (about 600° C.) at the intersection of the arrow B3 and the line of P=-0.0037T+11.301.
[0181] When the above-mentioned pretreatment process is performed, the hexagonal boron nitride powder after the pretreatment process is heated and pressurized to a temperature of 1900° C. or more and 2400° C. or less and a pressure of 8 GPa or more, starting from the final reaching temperature and reaching pressure of the pretreatment process, through the temperature and pressure within the stable region of wurtzite boron nitride. In this case, in the heating and pressurizing process, the penetration temperature into the stable region of wurtzite boron nitride is also 600° C. or more.
[0182] In the heating and pressing process, the penetration temperature into the stable region of wurtzite boron nitride is above 600°C. As a result, the hexagonal boron nitride powder is converted into wurtzite boron nitride in an environment that easily causes atomic diffusion, and then converted into cubic boron nitride. Therefore, in the obtained cubic boron nitride sintered body, lattice defects are reduced, and the strength and toughness of the cubic boron nitride sintered body are improved. Therefore, the tool using the cubic boron nitride sintered body can have a long tool life even in the high-efficiency processing of high-strength cast iron materials.
[0183] The penetration temperature into the stable region of wurtzite boron nitride is preferably 900° C. or higher, more preferably 1200° C. or higher. The higher the penetration temperature, the easier it is for atomic diffusion to occur and the less lattice defects there are. The upper limit of the penetration temperature can be set to 1500° C. or lower, for example.
[0184] The pressure reached in the heating and pressing process is 8 GPa or more. The upper limit of the pressure reached is not particularly limited, and can be set to 15 GPa or less, for example. In the heating and pressing process, it is preferred that the pressure is increased to 10 GPa or more after penetrating into the stable region of wurtzite boron nitride.
[0185] In the heating and pressing step, the time for maintaining the temperature and pressure within the stable region of wurtzite-type boron nitride can be set to, for example, 5 minutes to 60 minutes.
[0186] In the heating and pressing process, Figure 2 , Figure 3 In the path, heating is followed by pressurization, and further heating is performed, but it is not limited thereto. The method of heating and pressurization is not particularly limited as long as it can make the penetration temperature into the stable region of wurtzite boron nitride be 600° C. or more. For example, heating and pressurization can be performed simultaneously.
[0187] As described above, by subjecting the hexagonal boron nitride powder to a heating and pressurizing step, a cubic boron nitride sintered body can be obtained.
[0188] <Temperature and pressure maintenance process>
[0189] After the heating and pressing step, the cubic boron nitride sintered body obtained by the heating and pressing step may be kept for more than 10 minutes at a temperature of 1900° C. to 2400° C. (hereinafter, also referred to as “sintering temperature”) and a pressure of 8 GPa or more (hereinafter, also referred to as “sintering pressure”). As a result, the content of cubic boron nitride in the obtained cubic boron nitride sintered body becomes larger, and a longer tool life can be achieved.
[0190] The sintering temperature in the temperature and pressure holding step is preferably 1900° C. to 2400° C., more preferably 2100° C. to 2300° C. The sintering pressure in the temperature and pressure holding step is preferably 8 GPa to 15 GPa, more preferably 9 GPa to 12 GPa. The sintering time in the temperature and pressure holding step is preferably 10 minutes to 60 minutes, more preferably 10 minutes to 30 minutes.
[0191] < Figure 2 , Figure 3 Characteristics of cubic boron nitride sintered bodies obtained by the path>
[0192] exist Figure 2 In the path of , the penetration temperature into the stable region of wurtzite boron nitride is about 1200°C. As a result, the hexagonal boron nitride powder is converted into wurtzite boron nitride in an environment that easily causes atomic diffusion. Therefore, wurtzite boron nitride has fewer lattice defects and a very low dislocation density. After that, the wurtzite boron nitride is further heated and converted into a cubic boron nitride sintered body. Therefore, the dislocation density of the obtained cubic boron nitride sintered body is very low.
[0193] exist Figure 3 In the path of , the penetration temperature into the stable region of wurtzite boron nitride is about 600°C. As a result, the hexagonal boron nitride powder is converted into wurtzite boron nitride in an environment where atomic diffusion occurs. Therefore, wurtzite boron nitride has fewer lattice defects and lower dislocation density. After that, the wurtzite boron nitride is further heated and converted into a cubic boron nitride sintered body. Therefore, the dislocation density of the obtained cubic boron nitride sintered body is low.
[0194] If through Figure 2 The cubic boron nitride sintered body obtained by the path of Figure 3 Compared with the cubic boron nitride sintered body obtained by the path Figure 2 The dislocation density of the cubic boron nitride sintered body obtained by the path is low. It is believed that the reason is that Figure 2The penetration temperature of the path into the stable region of wurtzite boron nitride is higher, which easily causes atomic diffusion.
[0195] Example
[0196] The present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to these examples.
[0197] [Test Example 1]
[0198] <Sample 1 to Sample 27>
[0199] (Preparation process)
[0200] Hexagonal boron nitride powder (referred to as "hBN" in Tables 1 and 2) having an average particle size of 10 μm and a bonding material powder having a composition shown in the "Binder powder" column in the "Preparation process" in Tables 1 and 2 were prepared. For example, in Sample 1, TiC, Ti, and Al were prepared as bonding material powders.
[0201] The mixing ratio of hexagonal boron nitride powder and bonding material powder is adjusted so that the proportion of cubic boron nitride particles in the final cubic boron nitride sintered body is the proportion recorded in the "cBN particles (volume %)" column of "cubic boron nitride sintered body" in Tables 1 and 2.
[0202] The hexagonal boron nitride powder and the binder powder were mixed for 5 hours using a ball mill to obtain a mixed powder, which was then heat treated at 2050° C. in a nitrogen atmosphere to remove impurities (high temperature purification treatment).
[0203] (Pre-treatment process)
[0204] The mixed powder is placed in a sealed container made of molybdenum, and pressurized to a pressure of 5 GPa (recorded in the "First Pressurization" column of the "Pretreatment Process" in Table 1 and Table 2) at 25°C (room temperature, recorded in the "First Temperature" column of the "Pretreatment Process" in Table 1 and Table 2) using an ultra-high pressure and high temperature generator.
[0205] (Heating and Pressurizing Process)
[0206] For samples 1 to 26, the temperature in the ultra-high pressure and high temperature generator was heated to the temperature described in the "Second Temperature (wBN Intrusion Temperature)" column of the "Heating and Pressurizing Process" in Tables 1 and 2. During this period, the pressure in the ultra-high pressure and high temperature generator was maintained at the pressure described in the "First Pressurization" column of the "Pretreatment Process" in Tables 1 and 2.
[0207] Next, the pressure in the ultra-high pressure and high temperature generator is increased to the pressure recorded in the "Second Pressing" column of the "Heating and Pressing Process" in Tables 1 and 2. During this period, the temperature and pressure in the ultra-high pressure and high temperature generator are changed from the temperature and pressure in the stable region of hexagonal boron nitride to the temperature and pressure in the stable region of wurtzite boron nitride. In this heating and pressing process, the penetration temperature into the stable region of wurtzite boron nitride is the temperature recorded in the "Second Temperature (wBN Penetration Temperature)" column of the "Heating and Pressing Process" in Tables 1 and 2.
[0208] Next, the temperature in the ultra-high pressure and high temperature generator is heated to the temperature described in the "third temperature" column of the "temperature and pressure maintaining step" in Tables 1 and 2. During this period, the pressure in the ultra-high pressure and high temperature generator is maintained at the pressure described in the "second pressurization" column of the "heating and pressurizing step" in Tables 1 and 2.
[0209] Sample 27 was pressurized to the pressure (10 GPa) recorded in the "Second Pressing" column of the "Heating and Pressing Process" of Table 2 while maintaining the first temperature (25°C) of the pretreatment process. During this period, the temperature and pressure in the ultra-high pressure and high temperature generator changed from the temperature and pressure in the stable region of hexagonal boron nitride to the temperature and pressure in the stable region of wurtzite boron nitride. In this heating and pressing process, the penetration temperature into the stable region of wurtzite boron nitride is the temperature (25°C) recorded in the "Second Temperature (wBN Penetration Temperature)" column of the "Heating and Pressing Process" of Table 2.
[0210] Next, the temperature in the ultra-high pressure and high temperature generator is heated to the temperature (2200°C) recorded in the "third temperature" column of the "temperature and pressure maintaining step" in Table 2. During this period, the pressure in the ultra-high pressure and high temperature generator is maintained at the pressure (10 GPa) recorded in the "second pressurization" column of the "heating and pressurizing step" in Table 2.
[0211] (Temperature and pressure maintenance process)
[0212] The cubic boron nitride sintered bodies of Samples 1 to 27 were obtained by maintaining the temperature and pressure described in the "Third Temperature" and "Third Pressure" columns of the "Temperature and Pressure Maintaining Step" in Tables 1 and 2 for the time described in the "Retention Time".
[0213] <Sample 28>
[0214] The preparation process and the pretreatment process were performed in the same manner as for Sample 4. After the pretreatment process, the temperature and pressure in the ultrahigh pressure and high temperature generator were heated and pressurized to the temperature and pressure recorded in the "third temperature" and "third pressure" columns of the "temperature and pressure holding process" in Table 2 without passing through the wBN stable region, and the temperature and pressure were maintained for 30 minutes to obtain a cubic boron nitride sintered body of Sample 28.
[0215] <Evaluation>
[0216] (Composition of cBN sintered body)
[0217] The volume ratio of cBN particles to the binder phase in the cBN sintered body was measured. The specific measurement method is the same as the method described in the above-mentioned embodiment of the invention, so the description thereof will not be repeated. The results are shown in the "cBN particles (volume %)" and "binding phase (volume %)" columns of "cubic boron nitride sintered body" in Tables 1 and 2.
[0218] (Composition of the binding phase)
[0219] The composition of the binder phase in the cBN sintered body was determined by XRD. The results are shown in the "Binding Phase Composition" column of "Cubic Boron Nitride Sintered Body" in Tables 1 and 2.
[0220] (Dislocation density)
[0221] The dislocation density of cBN particles in the cBN sintered body was measured. The specific measurement method is the same as the method described in the method for implementing the above invention, so the description is not repeated. The results are shown in Table 1 and Table 2 for the "dislocation density of cBN particles ( / m 2 )" column.
[0222] (Cutting test)
[0223] The cBN sintered bodies of the prepared samples were used to prepare cutting tools (substrate shape: CNGA120408, blade edge treatment: T01215). The cutting tools were used to perform cutting tests under the following cutting conditions. The following cutting conditions are high-speed continuous processing of ductile iron, which is equivalent to high-efficiency processing of high-strength cast iron materials.
[0224] Cutting material: FCD700 (hardness: 250HB, profile cutting of round bars with V-grooves on the outer circumference)
[0225] Cutting speed: Vc = 500 m / min
[0226] Feed rate: f = 0.25 mm / rev.
[0227] Cutting amount: ap = 0.25 mm
[0228] Coolant: WET
[0229] Cutting method: End face continuous cutting
[0230] Evaluation method: The tool tip was observed every 1 minute of cutting time, and the cutting time at which the size of the notch reached 0.1 mm or more was taken as the tool life. The results are shown in the "Tool Life (minutes)" column of Tables 1 and 2.
[0231]
[0232]
[0233] <Inspection>
[0234] The cBN sintered bodies of Samples 2 to 7 and Samples 9 to 25 correspond to Examples.
[0235] In the cBN sintered body of Sample 1, the content of cBN particles is less than 40% by volume, which is equivalent to the comparative example. In the cBN sintered body of Sample 8, the content of cBN particles exceeds 96% by volume, and the dislocation density of cBN particles is 1×10 15 / m 2 The above is equivalent to a comparative example. In the cBN sintered bodies of Samples 26 to 28, the dislocation density of the cBN particles is 1×10 15 / m 2 The above corresponds to a comparative example.
[0236] It was confirmed that the tools using the cBN sintered bodies of Samples 2 to 7 and Samples 9 to 25 corresponding to the examples had a longer tool life than the tools using the cBN sintered bodies of Samples 1, 8, and Samples 26 to 28 corresponding to the comparative examples. This is believed to be because the thermal conductivity of Samples 2 to 7 and Samples 9 to 25 corresponding to the examples was improved, and the defect resistance of the rake face of the tool was improved.
[0237] In Sample 1, it is presumed that the dislocation density of cBN particles is small, but the content of cBN particles is too low at 35% by volume, so the hardness is insufficient and defects are likely to occur.
[0238] It is presumed that in Sample 8, since the content ratio of cBN particles is high, the dislocation density of the cBN particles is high, and defects are likely to occur.
[0239] According to Samples 9 to 22, it was confirmed that even when the types of the bonding materials of the cBN sintered bodies were set as shown in Tables 1 and 2, the tool life of the tool using the cBN sintered bodies was long.
[0240] Comparison of Sample 4, Sample 24, and Sample 25 shows that, in the heating and pressing step, the higher the penetration temperature into the stable region of wBN, the smaller the dislocation density of the cBN particles is, and the longer the tool life is.
[0241] In the heating and pressing process, the penetration temperature into the stable region of wBN was low in Samples 26 and 27, the dislocation density of cBN particles increased, and the tool life was reduced. It is believed that in Samples 26 and 27, atomic diffusion was difficult to occur when converting from hBN to wBN in the heating and pressing process, so the dislocation density increased.
[0242] Sample 28 did not pass through the stable region of wBN during the manufacturing process, the dislocation density of cBN particles increased, and the tool life decreased. It is believed that in Sample 28, although hBN was directly transformed into cBN during the manufacturing process, since the crystal structures of hBN and cBN are very different, lattice defects are easily generated during the phase transition, so the dislocation density increased.
[0243] [Test Example 2]
[0244] <Sample 4>
[0245] Sample 4 is the same cBN sintered body as Sample 4 of Test Example 1 described above.
[0246] <Sample 29>
[0247] (Preparation process)
[0248] Cubic boron nitride powder (referred to as "cBN" in Table 3) having an average particle size of 2 μm and binder powder having a composition shown in the "Binder powder" column of "Preparation step" in Table 3 were prepared. cBN powder prepared by a method using a known catalyst was prepared.
[0249] It is known that cubic boron nitride powder is produced by treating hexagonal boron nitride and a catalyst under high temperature and high pressure, which are thermal stability conditions of cBN. As a catalyst, an alkali metal element (lithium), an alkaline earth metal element (magnesium, calcium, strontium, beryllium, barium), etc. are generally used. Therefore, the obtained cubic boron nitride powder contains the catalyst element.
[0250] The mixing ratio of cubic boron nitride powder and binder powder is adjusted so that the proportion of cubic boron nitride particles in the final cubic boron nitride sintered body is the proportion recorded in the "cBN particles (volume %)" column of "cubic boron nitride sintered body" in Table 3.
[0251] The cubic boron nitride powder and the binder powder were mixed for 5 hours using a ball mill to obtain a mixed powder, which was then heat treated at 2050° C. in a nitrogen atmosphere to remove impurities (high temperature purification treatment).
[0252] (Pre-treatment process)
[0253] The mixed powder is placed in a sealed container made of molybdenum and pressurized to a pressure of 5 GPa (recorded in the "First Pressurization" column of the "Pretreatment Process" in Table 3) at 25°C (room temperature, recorded in the "First Temperature" column of the "Pretreatment Process" in Table 3) using an ultra-high pressure and high temperature generator.
[0254] (Heating and Pressurizing Process)
[0255] Next, while maintaining the temperature in the ultra-high pressure and high temperature generator at 25°C, the pressure is increased to 6 GPa (recorded in the "second pressure" column of the "heating and pressing process" in Table 3). During this period, the temperature and pressure in the ultra-high pressure and high temperature generator change from the temperature and pressure in the stable region of hexagonal boron nitride to the temperature and pressure in the stable region of wurtzite boron nitride. In this heating and pressing process, the penetration temperature into the stable region of wurtzite boron nitride is 25°C (recorded in the "second temperature (wBN penetration temperature)" column of the "heating and pressing process" in Table 3).
[0256] Next, the temperature in the ultra-high pressure and high temperature generator was heated to 1400°C (recorded in the "third temperature" column of the "temperature and pressure maintaining process" in Table 3). During this period, the pressure in the ultra-high pressure and high temperature generator was maintained at 6 GPa (recorded in the "second pressurization" column of the "heating and pressurizing process" in Table 3).
[0257] (Temperature and pressure maintenance process)
[0258] The temperature of 1400°C and the pressure of 6 GPa in the ultra-high pressure and high temperature generator were maintained for 30 minutes (recorded in the "holding time" column of the "temperature and pressure holding process" in Table 3) to obtain a cubic boron nitride sintered body of sample 29.
[0259] <Sample 30>
[0260] (Preparation process)
[0261] In Sample 30, a cubic boron nitride sintered body was produced by the same method as Sample 4, except that a reversed hexagonal boron nitride powder (hereinafter also referred to as "reverse hBN powder") produced by the following steps was used as a raw material powder instead of hBN powder. The reversed hBN powder was produced by heat-treating the cubic boron nitride powder prepared in Sample 29 at 1600°C to reversely convert cBN into hBN.
[0262] <Evaluation>
[0263] (Composition of cBN sintered body, composition of binder phase, dislocation density of cBN particles)
[0264] The composition of the cBN sintered body, the composition of the binder phase, and the dislocation density of the cBN particles were confirmed for the produced cBN sintered body. The specific measurement method is the same as the method described in the above-mentioned embodiment of the invention, so the description thereof will not be repeated. The results are shown in Table 3.
[0265] (Catalyst element content)
[0266] The catalyst element content in the produced cBN sintered body was measured by high frequency induction plasma emission spectrometry (ICP emission spectrometry) using an instrument: "ICPS-8100" (trademark) manufactured by Shimadzu Corporation. Specifically, the measurement was performed according to the following procedure.
[0267] First, the cubic boron nitride sintered body was immersed in fluorinated nitric acid in a sealed container for 48 hours to dissolve the binder phase in the fluorinated nitric acid. The cubic boron nitride particles remaining in the fluorinated nitric acid were subjected to high frequency induction plasma emission spectrometry to measure the content of each catalyst element.
[0268] (Cutting test)
[0269] The cBN sintered bodies of the prepared samples were used to prepare cutting tools (substrate shape: CNGA120408, blade edge treatment T01215). The cutting tools were used to perform cutting tests under the same cutting conditions as in Test Example 1. The cutting conditions were high-speed continuous machining of ductile iron, which is equivalent to high-efficiency machining of high-strength cast iron materials. The results are shown in the "Tool Life" column of Table 3.
[0270]
[0271] <Inspection>
[0272] The cBN sintered bodies of Samples 4 and 30 correspond to Examples.
[0273] In the cBN sintered body of Sample 29, the dislocation density of cBN particles is 1×10 15 / m 2 The above corresponds to a comparative example.
[0274] It was confirmed that the tool using the cBN sintered body of Sample 4 and Sample 30 corresponding to the embodiment had a longer tool life than the tool using the cBN sintered body of Sample 29 corresponding to the comparative example. This is believed to be because the thermal conductivity of Sample 4 and Sample 30 corresponding to the embodiment was improved, and the defect resistance of the rake face of the tool was improved.
[0275] According to Sample 30, it was confirmed that the cBN sintered body has excellent tool performance even when it contains a trace amount of catalyst elements.
[0276] As mentioned above, although the embodiment and the example of this disclosure were described, it is also planned from the beginning that the configurations of each embodiment and the example described above are appropriately combined or variously modified.
[0277] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.
Claims
1. A method for producing a cubic boron nitride sintered body, comprising: A process of preparing hexagonal boron nitride powder and bonding material powder; and The hexagonal boron nitride powder and the binder powder are heated and pressurized to a temperature of 1900° C. to 2400° C. and a pressure of 8 GPa or more at a temperature and pressure within the stable region of wurtzite boron nitride. The stable region of wurtzite boron nitride is a region that satisfies the following equation 1 and the following equation 2 simultaneously when the temperature is set to T°C and the pressure is set to PGPa. Formula 1: P ≥ -0.0037T + 11.301 Formula 2: P≤-0.085T+117 In the heating and pressurizing step, the penetration temperature into the stable region of the wurtzite boron nitride is 600° C. or higher. The cubic boron nitride sintered body comprises 40 volume % or more and 96 volume % or less of cubic boron nitride particles and 4 volume % or more and 60 volume % or less of a binding phase. The dislocation density of the cubic boron nitride particles is 1×10 14 / m 2 More than and less than 1×10 15 / m 2 .
2. The method for producing a cubic boron nitride sintered body according to claim 1, wherein: The method for producing a cubic boron nitride sintered body includes, before the step of heating and pressing, a step of pressurizing the hexagonal boron nitride powder to a pressure of 0.5 GPa to 6 GPa while maintaining the temperature in a range of -50°C to 100°C.
3. The method for producing a cubic boron nitride sintered body according to claim 1 or 2, wherein: The penetration temperature into the stable region of the wurtzite boron nitride is 900° C. or higher.
4. The method for producing a cubic boron nitride sintered body according to claim 3, wherein: The penetration temperature into the stable region of the wurtzite boron nitride is 1200° C. or higher.
5. The method for producing a cubic boron nitride sintered body according to claim 1 or 2, wherein: The penetration temperature into the stable region of the wurtzite boron nitride is 1500° C. or less.
6. The method for producing a cubic boron nitride sintered body according to claim 1 or 2, wherein: In the heating and pressurizing step, the holding time at the temperature and pressure within the stable region of wurtzite-type boron nitride is 5 minutes to 60 minutes.
7. The method for producing a cubic boron nitride sintered body according to claim 1 or 2, wherein: The method for producing a cubic boron nitride sintered body includes, after the heating and pressing step, the step of maintaining the cubic boron nitride sintered body obtained by the heating and pressing step under conditions of a temperature of 1900° C. to 2400° C. and a pressure of 8 GPa or more for 10 minutes or more.
Citation Information
Patent Citations
High-strength high-thermal conductivity cubic boron nitride sintered compact
JP2005187260A
Cubic boron nitride composite sintered body, production method of the same and cutting tool, abrasion-resistant tool and grinding tool
JP2015202980A
Cubic boron nitride composite sintered body, production method thereof and cutting tool, abrasion-resistant tool and grinding tool
JP2015202981A
Cubic boron nitride sintered compact
WO2005066381A1
Tool comprising sintered cubic boron nitride
WO2012053375A1